The virtual stuntman: dynamic characters with a repertoire of autonomous motor skills - Faloutsos, Petros; van de Panne, Michiel; Terzopoulos, Demetri (Computers & graphics, 2001)
An ambitious goal in the area of physics-based computer animation is the creation of virtual actors that autonomously synthesize realistic human motions and possess a broad repertoire of lifelike motor skills. To this end, the control of dynamic, anthropomorphic figures subject to gravity and contact forces remains a difficult open problem. In this paper, we report on our ongoing development of a virtual stuntman, a dynamic graphical character that possesses a nontrivial repertoire of lifelike motor skills. The repertoire includes basic actions such as balance, protective stepping when balance is disturbed, protective arm reactions when falling, multiple ways of rising upright after a fall, and several more vigorously dynamic motor skills. Our virtual stuntman is the product of a recently proposed framework for integrating motor controllers, which includes among other ingredients an explicit model of pre-conditions; i.e., those regions of a dynamic figure's state space within which a given motor controller is applicable and expected to work properly.